Contribution of Human Development Index and Environmental Quality to Poverty in Indonesia - Anisa Mawaddah Nst; Isnaini Harahap; Kamilah (Jurnal Manajemen Bisnis, 2024)
Poverty has long been a national problem, which until now still shows no signs of ending. Poverty is one of the fundamental problems that is the center of attention of the government in all provinces of Indonesia. In almost all developing countries, the standard of living of the majority of the Indonesian population tends to be very low. A low standard of living can create a form of poverty. The aim of this research is to determine the influence of GRDP, HDI and Environmental Quality on Poverty in Indonesia. The type of approach in this research is quantitative. The sample in this research is data from 4 variables in Indonesia for the 2018-2022 period. The analysis method used is panel data regression. The object of research is the island of Sumatra which consists of 10 provinces. The results of data testing explain that HDI has an effect and Environmental Quality has no effect on Poverty.